2015
DOI: 10.1063/1.4932057
|View full text |Cite
|
Sign up to set email alerts
|

A sound idea: Manipulating domain walls in magnetic nanowires using surface acoustic waves

Abstract: We propose a method of pinning and propagating domain walls in artificial multiferroic nanowires using electrically induced surface acoustic waves. Using finite-element micromagnetic simulations and 1D semi-analytical modelling, we demonstrate how a pair of interdigitated acoustic transducers can remotely induce an array of attractive domain wall pinning sites by forming a standing stress/strain wave along a nanowire's length. Shifts in the frequencies of the surface acoustic waves allow multiple domain walls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 30 publications
0
52
0
3
Order By: Relevance
“…A possibility to drive a domain wall by electrically induced surface acoustic waves (SAWs) has been demonstrated recently. 27,28 Such studies pave the way for various applications in magnetic memory and logic devices. 26,32,33 In this work, we explore a skyrmion bubble dynamics induced by counter-propagating SAWs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A possibility to drive a domain wall by electrically induced surface acoustic waves (SAWs) has been demonstrated recently. 27,28 Such studies pave the way for various applications in magnetic memory and logic devices. 26,32,33 In this work, we explore a skyrmion bubble dynamics induced by counter-propagating SAWs.…”
mentioning
confidence: 99%
“…23,24 Since the modulation of anisotropy by strain is observed in many ferromagnetic materials, strain can also be used to control magnetization dynamics. [25][26][27][28][29][30][31] Thus, one can also electrically control magnetization dynamics by combining piezoelectric and magnetoelastic effects. A possibility to drive a domain wall by electrically induced surface acoustic waves (SAWs) has been demonstrated recently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface acoustic waves have also been proposed as an alternative method for synchronously propagating and pinning domain walls in magnetic nanowires for applications in racetrack memory devices. 11,12 It was found that the velocity of propagation of the domain walls depends on the amplitude of the SAW. In the area of microfluidics, recent research demonstrates that SAWs provide an effective means to manipulate fluids (fluid mixing, [13][14][15] translation, [16][17][18] jetting, 19 and atomization 20 ) and manipulate particles (handling, 21 focusing, 22 separation, 23,24 sorting, 25,26 concentration, [27][28][29][30] and reorientation 31 ) in lab-on-a-chip devices for applications in chemistry, biology, and medicine.…”
mentioning
confidence: 99%
“…Among these applications are the acoustic manipulation and readout of magnetic memory elements [1][2][3][4] , acoustic driving of magnetic domain walls 5 , the acoustic generation of resonant spin-wave excitations [6][7][8][9][10][11][12][13][14] , and magnetic field detectors. 15, 16 Some of the interest rests on the point that acoustical wavelengths range in the sub-micron to micron scale at the gigahertz frequencies typical of spin-wave resonance.…”
mentioning
confidence: 99%